Regional Economic Outlook, April 2021, Middle East and Central Asia. (International Monetary Fund, 2021)
A year into the coronavirus (COVID-19) pandemic, the race between vaccine and virus entered a new phase in the Middle East and Central Asia, and the path to recovery in 2021 is expected to be long and divergent. The outlook will vary significantly across countries, depending on the pandemic's path, vaccine rollouts, underlying fragilities, exposure to tourism and contact-intensive sectors, and policy space and actions. 2021 will be the year of policies that continue saving lives and livelihoods and promote recovery, while balancing the need for debt sustainability and financial resilience. At the same time, policymakers must not lose sight of the transformational challenges to build forward better and accelerate the creation of more inclusive, resilient, sustainable, and green economies. Regional and international cooperation will be key complements to strong domestic policies.